Impact of feeding problems on nutritional intake and growth: Oxford Feeding Study II. - Sullivan, P; Juszczak, E; Lambert, B; Rose, M; Ford-Adams, M; Johnson, A (2002)
Poor nutritional status and growth failure are common in children with cerebral palsy (CP). The aim of this study was to assess, within a subgroup of a large and clearly defined population of children with disabilities, the impact of feeding difficulties on (1) the quality (micronutrient intake) and quantity (macronutrient intake) of their diet and (2) their growth. One hundred children with disabilities (40 females, 60 males; mean age 9 years, SD 2 years 5 months; range 4 years 6 months to 13 years 7 months) underwent a detailed dietetic analysis and a comprehensive anthropometric assessment. Diagnostic categories of disability were: CP (n=90); global developmental delay (n=3); Marfan syndrome (n=1); intractable epilepsy (n=2); agenesis of the corpus callosum (n=2); methyl malonic aciduria (n=1); and congenital rubella (n=1). Neurological impairment was classified according to difficulty with mobility which was graded as mild (little or no difficulty walking), moderate (difficulty walking but does not need aids or a helper), and severe (needs aids and/or a helper or cannot walk). Results confirmed the significant impact of neurological impairment in children on body growth and nutritional status becoming worse in those with a greater degree of motor impairment. The major nutritional deficit was in energy intake, with only one fifth reportedly regularly achieving over 100% estimated average requirement (EAR), whilst micronutrient intake was less markedly impaired and protein intake was normal in this group (96% above EAR). Many children with neurological impairment would benefit from individual nutritional assessment and management as part of their overall care.